Strategic Analysis of Sports Tourism Marketing Mix in Mazandaran with 7P\'s Approach - shahab hasibi; vahid shojaei (تحقیقات کاربردی علوم جغرافیایی)
The development and improvement of the tourism industry in the country or its various regions depends on effective marketing mechanisms. Marketing is an instrument for promoting sport tourism in different regions, which should be carefully considered. The purpose of this study was to analyze the strategic combination of sports tourism marketing in Mazandaran province with a 7 P's approach. 235 managers of sport and tourism organizations, managers of tourism offices, tourism guides and academic experts in the fields of sport and tourism management, as a sample of this research, were randomly selected, completed a researcher-made questionnaire composed of 57 valid questions & 7 Component (α=0.792) voluntarily. Findings from Friedman test showed that the Components of sports tourism mix marketing in the province based on priority were significant. The element of price (mean 4.69) is the highest priority and the process or planning (mean 3.69)  is the lowest priority. Other elements of the sport tourism mix marketing of the province are the priority, respectively: product or service (mean 4.21), place (mean 4.05), physical evidence (mean 3.91), people (mean 3.76) and promotion(mean 3.61). Findings from Friedman test showed that the elements of sports tourism marketing mix in the province based on priority were significant. The element of price is the highest priority and the process or planning is the lowest priority. Other elements of the sport tourism marketing mix of the province are the priority, respectively: product or service, place, physical evidence, people and promotion.